Sistem Pendukung Keputusan Penentuan Organisasi Kemahasiswaan Terbaik Dengan Metode Vikor (Studi Kasus: STMIK Budi Darma) - Khairul Habibi Harahap (Journal of Information System Research (JOSH), 2020)
This Decision Support System is to make it easier for each student to choose an organization that is in accordance with the wishes of each student, so that students will not regret later when they have joined as members or administrators of the organization itself. The organization is a group of people who work together for a common goal and can also be a forum for people to gather and work together rationally and systematically, planned, guided and controlled, in developing interests and talents as the goals of the organization itself. VIKOR (VIseKriterijumska Optimizacija I Kompromisno Resenje) is a multi-criteria optimization method used in complex systems. This method focuses on ranking and choosing from a set of alternatives, and specifies a compromise solution to the problem of conflicting criteria, which can help decision makers to reach the final decision. Here, a compromise solution is a viable solution that is closest to the ideal, and compromise means an agreement is established with mutual concessions.